2020
DOI: 10.1038/s41386-020-00908-0
|View full text |Cite
|
Sign up to set email alerts
|

Phase 1 randomized study on the safety, tolerability, and pharmacodynamic cognitive and electrophysiological effects of a dopamine D1 receptor positive allosteric modulator in patients with schizophrenia

Abstract: ASP4345, a novel dopamine D1 receptor positive allosteric modulator, is being evaluated for the treatment of cognitive impairment associated with schizophrenia (CIAS). This phase 1 multiple ascending-dose study (NCT02720263) assessed the safety, tolerability, and pharmacodynamics of ASP4345 in patients with schizophrenia/schizoaffective disorder. Pharmacodynamic assessments were Cogstate cognitive tests and electrophysiological biomarkers, including gamma-band power and phase synchronization in response to 40-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(14 citation statements)
references
References 38 publications
(57 reference statements)
0
14
0
Order By: Relevance
“…Over the past decade, much of the focus on D1Rs in schizophrenia has been on augmenting their signaling to promote cognition [56][57][58][59] . This idea is largely based on foundational work showing that, in schizophrenia, dopamine transmission is decreased within the prefrontal cortex, p. 16 where D1Rs are enriched and their signaling is crucial for cognitive function 60,61 .…”
Section: Therapeutically Targeting Hyperdopaminergic D1-spn Dynamicsmentioning
confidence: 99%
“…Over the past decade, much of the focus on D1Rs in schizophrenia has been on augmenting their signaling to promote cognition [56][57][58][59] . This idea is largely based on foundational work showing that, in schizophrenia, dopamine transmission is decreased within the prefrontal cortex, p. 16 where D1Rs are enriched and their signaling is crucial for cognitive function 60,61 .…”
Section: Therapeutically Targeting Hyperdopaminergic D1-spn Dynamicsmentioning
confidence: 99%
“…[90] Besides, they are found to show decreased or no receptor desensitisation compared to orthosteric agonists. [90] This class of drug is important in preventing and/or treating cognitive impairment, [89] schizophrenia, [91] depression, [92] Parkinson's disease, [93] Alzheimer's disease, [92] Huntington's disease [88] and attention deficit hyperactivity disorder. [94] Astellas Pharma Inc. discovered benzoxazole derivatives that are useful as dopamine D1 receptor PAMs.…”
Section: Dopamine D1 Receptor Positive Allosteric Modulator (Pam)mentioning
confidence: 99%
“…For instance, in transgenic mice over-expressing D1 receptors, the D1-receptor PAM DETQ led to improved performance in an object recognition task and in cortical ACH release [392]. A phase 1 clinical trial with the D1receptor PAM ASP4345 showed improvements in psychomotor function, visual attention and corresponding improvements in neurophysiological markers [393].…”
Section: Dopaminergic Systemmentioning
confidence: 99%